Analisis Instrumen Tes Penilaian Pendidikan Agama Islam Menggunakan Tes Teori Klasik - Boini Boini; Sahrul Sahrul; Asmanah Asmanah; Sumin Sumin (At Turots: Jurnal Pendidikan Islam, 2023)
The aim of the research is to find out and describe Validity, Reliability and Distinction. The level of difficulty is an important instrument in education so that the resulting data can be used well. Validation is divided into validation of a content, construct. Content validation is an instrument that can be said to be valid if it is in accordance with the curriculum, material and objectives of a lesson. Meanwhile, construct validity is validity that uses patterns to think about how achieved test items can measure something that will be measured and adjusted to the concept that has been determined. Reliability is determined by the Cronbach's alpha value, if the Cronbach's alpha value is 0.5 it can be used for research purposes. Discriminating power is the ability to differentiate between upper and lower groups in the form of questions. The level of difficulty differentiates questions in terms of difficulty.